Induction of Adventitious Roots from Leaf Explants of Talinum fruticosum (L.) Juss. through the Application of Different IBA Concentrations In Vitro - Putri, Suci Indah; Noli, Zozy Aneloi; Idris, M. (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effect of indole-3-butyric acid (IBA) concentrations on adventitious root induction from Talinum fruticosum leaf explants under in vitro conditions. The experiment was conducted using a completely randomized design with three IBA concentrations (2, 4, and 6 mg/L) and 20 replicates for each treatment. Leaf explants with an approximate diameter of 1.5 cm were cultured on Murashige and Skoog (MS) medium supplemented with IBA and observed for approximately 30 days. The evaluated parameters included explant survival percentage, root induction percentage, root initiation time, root number, root length, and root biomass (fresh and dry weight). Data were analyzed using analysis of variance (ANOVA). The results showed that IBA supplementation significantly affected root initiation time, with the fastest root emergence occurring after 8 days, and promoted root elongation, reaching a maximum root length of 1.23 cm. Explant survival and root induction percentages reached 100% in all treatments, indicating no significant differences among IBA concentrations. However, IBA application did not significantly affect root number or root biomass. Among the treatments, 2 mg/L IBA exhibited the best response by accelerating root initiation and increasing root length compared with the other concentrations. Therefore, the application of IBA at 2 mg/L effectively optimized selected parameters associated with adventitious root induction in T. fruticosum under in vitro conditions.